Control of Postharvest Blue and Green Molds of Oranges by Hot Water, Sodium Carbonate, and Sodium Bicarbonate - Palou, Lluís; Smilanick, Joseph L.; Usall, Josep; Vinas, Inmaculada (American Phytopathological Society (APS), 2021)
Control of citrus blue mold, caused by Penicillium italicum, was evaluated on artificially inoculated oranges immersed in water at up to 75°C for 150 s; in 2 to 4% sodium carbonate (wt/vol) at 20 or 45°C for 60 or 150 s; or in 1 to 4% sodium bicarbonate at room temperature for 150 s, followed by storage at 20°C for 7 days. Hot water controlled blue mold at 50 to 55°C, temperatures near those that injured fruit, and its effectiveness declined after 14 days of storage. Sodium carbonate and sodium bicarbonate were superior to hot water. Temperature of sodium carbonate solutions influenced effectiveness more than concentration or immersion period. Sodium carbonate applied for 150 s at 45°C at 3 or 4% reduced decay more than 90%. Sodium bicarbonate applied at room temperature at 2 to 4% reduced blue mold by more than 50%, while 1% was ineffective. In another set of experiments, treatments of sodium bicarbonate at room temperature, sodium carbonate at 45°C, and hot water at 45°C reduced blue mold incidence on artificially inoculated oranges to 6, 14, and 27%, respectively, after 3 weeks of storage at 3°C. These treatments reduced green mold incidence to 6, 1, and 12%, respectively, while incidence among controls of both molds was about 100%. When reexamined 5 weeks later, the effectiveness of all, particularly hot water, declined. In conclusion, efficacy of hot water, sodium carbonate, and sodium bicarbonate treatments against blue mold compared to that against green mold was similar after storage at 20°C but proved inferior during long-term cold storage.